Introduction of Universal Newborn Screening for Sickle Cell Disease in Germany-A Brief Narrative Review - Stephan Lobitz; Joachim B. Kunz; Holger Cario; Dani Hakimeh; Andrea Jarisch; Andreas E. Kulozik; Lena Oevermann; Regine Grosse (MDPI AG, 2021)
Sickle cell disease (SCD) is a severe non-malignant disorder of hemoglobin and is inherited in an autosomal-recessive manner [...]